Jekel's epidemiology, biostatistics, preventive medicine, and public health - Joann G. Elmore; Dorothea M. G. Wild; Heidi D. Nelson; David L. Katz; Elsevier (Firm) (St. Louis Missouri : Elsevier, 2020)
Jekel's Epidemiology, Biostatistics, Preventive Medicine, and Public Health is the only textbook that combines the disciplines of medical epidemiology, biostatistics, preventive medicine, and public health in one convenient resource. Written by renowned epidemiologists and public health experts, this text presents the information with a clinical focus, using real-life medical examples throughout. With review questions in each chapter to maximize knowledge retention and target key areas of review, it serves as an outstanding resource for USMLE prep - and is recommended by the American Board of Preventive Medicine as a top review source for its core specialty examination
Keywords: Biometry; biometrics; Public Health; Preventive Medicine; Medical statistics; Epidemiologic Methods